Current and future geodetic activities in Malaysia - A. K., Abd. Majid; Ses, Sahrum; Hisham, Abdullah; Abu, Samad (2002)
Malaysia covers an area of about 329,758 square kilometers, consisting of 12 states in Peninsular Malaysia and 3 states in the Borneo Island. South China Sea separates the two regions by about 540 km. Peninsular Malaysia, covering 131,598 sq. km. has its frontiers with Thailand and Singapore while the states in Borneo Island covering 198,160 sq. km, borders the territory of Indonesia’s Kalimantan to the South and Brunei to the North. Malaysia lies close to the equator between latitudes of 1° and 7°N and longitudes of 100° and 119°E. The Dept. of Survey and Mapping, Malaysia (DSMM) traces its origin back in 1886. The 1880s also marked an important phase with the commencement of more widespread trigonometrically works in various parts of Malaya. Lieutenant Woore of the Royal Navy made the first attempt at triangulation survey in Penang in 1832. The intensive methods of conventional geodetic surveys have basically ceased with the advent of GPS. In the subsequent years, there have been numerous geodetic projects implemented by DSMM on a nation wide scale. Collectively, these projects were and are executed with the final aim of providing horizontal and vertical controls for the development of various infrastructures across the country. In Malaysia, research in geodesy is undertaken through academic institutions, principaally funded by the Ministry of Science, Malaysia. Information about the national geodetic infrastructure and databases can be obtained from the Geodesy Section, Geodetic Division, DSMM. This paper will describe the various geodetic activities that has been and currently undertaken by DSMM and Universiti Teknologi Malaysia.